A new governance for a new urban form (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
The crisis of Rome is not a local issue, it is not reduced to the problem of potholes or waste on the street, that is the things we read daily in the newspapers. What we need to understand is rather what Rome can become in the 21st century, how it can draw its role with respect to the political class, which is absent, and to the intermediate social class.